2004
DOI: 10.1109/tuffc.2004.1386682
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of lesion detectability in ultrasound images acquired using time-shift compensation and spatial compounding

Abstract: The effects of aberration, time-shift compensation, and spatial compounding on the discrimination of positive-contrast lesions in ultrasound b-scan images are investigated using a two-dimensional (2-D) array system and tissue-mimicking phantoms. Images were acquired within an 8:8 12-mm 2 field of view centered on one of four statistically similar 4-mm diameter spherical lesions. Each lesion was imaged in four planes offset by successive 45 rotations about the central scan line. Images of the lesions were acqui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Under these conditions, image artifacts are suppressed, while desired patterns preserved during averaging. Spatial compounding has consistently shown marked improvement in the contrast and perceived resolution of ultrasound images [3], [6]- [8]. However, standard spatial compounding does not distinguish between individual raw data sets that are averaged.…”
Section: B Spatial Compoundingmentioning
confidence: 99%
“…Under these conditions, image artifacts are suppressed, while desired patterns preserved during averaging. Spatial compounding has consistently shown marked improvement in the contrast and perceived resolution of ultrasound images [3], [6]- [8]. However, standard spatial compounding does not distinguish between individual raw data sets that are averaged.…”
Section: B Spatial Compoundingmentioning
confidence: 99%
“…Re cently, at ten tion has been given to com bin ing spa tial com pound ing and adap tive im aging. [23][24][25][26] The im ages formed from the subap er tures used in com pound ing are sig nif i cantly less cor re lated when ab er ra tions of siz able strength or low cor re la tion length are pres ent. This causes a larger re duc tion in speckle vari ance than would be ob tained by com pound ing with out ab er ra tion pres ent.…”
Section: Ta Blementioning
confidence: 99%
“…12 To date, most 3-D spatial compounding research reported in the literature has used a 1-D linear or phased array with mechanical translation and position tracking. 1317 1-D arrays lack the capability of electronic focusing in elevation which degrades the image quality away from the fixed focus. Additionally, mechanical translation with position tracking can introduce registration errors 12.…”
Section: Introductionmentioning
confidence: 99%